Soil fertility and nutrients in litter on a Semideciduous Seasonal Forest fragment - Godinho, Tiago de Oliveira; Caldeira, Marcos Vinicius Winckler; Rocha, José Henrique Tertulino; Caliman, Jônio Pizzol; Viera, Márcio (Revista Ecologia e Nutrição Florestal - ENFLO, 2014)
The objective of the study was to evaluate the soil fertility of a Submontane Seasonal Semideciduous Forest in three topographic gradients and correlate with the production and accumulation of these nutrients by litter, in the municipality of Cachoeiro de Itapemirim (ES). Soil samples for characterization of the 12 plots in the study were collected at a depth of 0 – 20 cm. The collection of production and accumulated litter were conducted on the same plots of soil sampling. In each plot were distributed five litter collectors, systematically allocated within the plot, one near each corner and the last, in the center. Collections were carried out monthly litter deposited on the collectors and accumulated on the floor of the forest, at random, with the aid of a template. The soil chemical properties were subjected to analysis of variance and subsequent comparison of means using the Tukey test at 5% probability. Analyses Spearman correlation and multiple linear regression models to assess the correlations between the attributes of litter and soil. The soils of the study area are generally medium to high fertility, with medium to high levels of organic matter and low phosphorus. The P, Ca and Mg in the soil available showed a significant positive correlation with the annual deposition of these nutrients by litterfall and average content of nutrients in the litter was correlated only with the level of available P in the soil.